THE PHENOMENON OF ECOLOGICAL CULTURE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In the period of renewal of the current education system, the necessity of forming environmental culture among students is becoming a demand of the time. In this article, concepts of ecological culture are given, and the factors of its manifestation and development are mentioned.